The Effects of Silicone Hydrogel Lens Wear on the Corneal Epithelium and Risk for Microbial Keratitis - Robertson, Danielle M. (2013)
Previous studies using animal models and human clinical trials have demonstrated that the use of low oxygen transmissible contact lens materials produce corneal epithelial surface damage resulting in increased Pseudomonas aeruginosa (PA) adhesion and raft-mediated internalization into surface corneal epithelial cells. These findings led to the testable clinical predictions that: (1) microbial keratitis (MK) risk is expected to be greatest during the first 6 months of wear; (2) there is no difference between 6 and 30 night extended wear; and (3) that wear of hyper-oxygen transmissible lenses would reduce the reported incidence of infection. Subsequent epidemiological studies have confirmed the first two predictions; however, increased oxygen transmissibility with silicone hydrogel (SiHy) lens wear has not altered the overall incidence of MK. In this review, more recent clinical and basic studies that investigate epithelial alterations and bacterial adhesion to corneal epithelial cells following wear of SiHy lenses with and without concomitant exposure to chemically preserved multipurpose solutions (MPS) will be examined. The collective results of these studies demonstrate that even in the absence of lens-related hypoxia, MPS induce ocular surface changes during SiHy lens wear which are associated with a pathophysiological increase in PA adherence and internalization in the corneal epithelium, and therefore, predict an increased risk for PA-MK. In addition, new data supporting an interactive role for inflammation in facilitating PA adherence and internalization in the corneal epithelium will also be discussed.